Optimalisasi Layanan Bimbingan Konseling melalui E-Konseling Berbasis Website dengan Metode Prototype pada SMP Negeri 20 Kota Jambi - Melia Citra Dewi; Noneng Marthiawati; Dian Safitri; Hafiz Nugraha (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Guidance and counseling services in schools play an important role in helping students address academic, social, and psychological problems; however, their conventional implementation still faces various obstacles, such as limited face-to-face time, students' reluctance to consult directly, and counseling data documentation that is still carried out manually. This study aims to design and build a website-based e-counseling system to optimize guidance and counseling services at SMP Negeri 20 Kota Jambi. This research uses the prototype method in the system development process, consisting of three main stages: listening to user needs, building and revising the prototype, and user testing, which are carried out repeatedly until the system is declared to meet the needs. The results show that the developed e-counseling system has features for online consultation, counseling scheduling, digital counseling history, and user access management. Functional testing results indicate that all system features function properly, and user acceptance testing results show positive responses, both in terms of ease of use and the system's benefits. This research has implications for improving the effectiveness of guidance and counseling services at SMP Negeri 20 Kota Jambi, particularly in terms of ease of consultation access, student comfort, and more structured counseling data documentation, making it a potential reference for the development of technology-based counseling services in other schools.